Necrotizing Granulomatous Pneumocystis Infection Presenting as a Solitary Pulmonary Nodule: A Case Report and Review of the Literature - Mansur Assaad; Mohamed Swalih; Apurwa Karki (Case Reports in Pulmonology)
Pneumocystis jirovecii is an opportunistic fungus that is classically associated with pneumonia in immunocompromised patients, particularly those with human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS). However, this infection is now more commonly seen in those with malignancy, particularly lymphoproliferative disorders. Classic image findings with Pneumocystis jirovecii pneumonia (PJP) include bilateral ground-glass opacities with or without cyst formation. Up to 5% of patients with PJP may present with atypical image findings, specifically nodular opacities or masses thought to represent granulomatous inflammation. The differential diagnosis for a new solitary pulmonary nodule in an immunocompromised patient is broad. One must first rule out a recurrence of malignancy or new primary malignancy. In our patient’s case, two nondiagnostic bronchoscopies with EBUS-TBNA eventually led to a surgical resection, which revealed a diagnosis of nodular necrotizing granulomatous Pneumocystis jirovecii. The diagnostic yield from EBUS is not well established, and most cases require surgical biopsy for definitive diagnosis. Further data regarding the use of EBUS-TBNA in diagnosing granulomatous PJP is needed.